STUDI TENTANG KUALITAS HUBUNGAN JANGKA PANJANG UNTUK MENINGKATKAN KINERJA PEMASARAN (STUDI PADA AGEN CV. GARUDA) - Utomo, Siswanto (Master of Management Diponegoro University, 2014)
This research was to answer research problem how to improve marketing performance throughlong-term relationship qualityin CV. Garuda and it agencies which analyze factors suspected,i.e.: trust, commitment, andsatisfaction.This research use 109 agencies of CV. Garuda. Data analysis tools used in this research isStructural Equation Modeling (SEM) under AMOS 5.The result of the data shows that research model has good fit and all the hypotheses can beproved. The conclusions are: trusthas positive influence to long-term relationship quality,commitmentlevel has positive influence to long-term relationship quality, and satisfaction haspositive influence to long-term relationship quality, and long-term relationship qualityhas positiveinfluence to marketing performance.